Graphdiyne‐Based Bulk Heterojunction for Efficient and Moisture‐Stable Planar Perovskite Solar Cells. Issue 30 (19th September 2018) - Li, Hongshi; Zhang, Rui; Li, Yusheng; Li, Yiming; Liu, Huibiao; Shi, Jiangjian; Zhang, Huiyin; Wu, Huijue; Luo, Yanhong; Li, Dongmei; Li, Yuliang; Meng, Qingbo
Abstract: Graphdiyne (GDY) is introduced into the FA0.85 MA0.15 Pb(I0.85 Br0.15 )3 perovskite film to construct a perovskite/graphdiyne (PVSK/GDY) bulk heterojunction for planar perovskite solar cells (PSCs). This PVSK/GDY bulk heterojunction is suggested to provide an extra channel to favor exciton separation and facilitate the photogenerated electron extraction ability. The electron transportation ability has been improved for higher J sc, and the introduction of GDY can passivate grain boundaries and interfaces to effectively suppress photogenerated carrier recombination, leading to relatively higher fill factor. Up to 20.54% power conversion efficiency is achieved. In addition, the ability of this perovskite film with PVSK/GDY bulk heterojunctions to function in humid conditions is also improved, leading to good stability of PSCs toward moisture. This work provides a new way to fabricate highly efficient, stable PSCs by constructing bulk heterojunctions simultaneously for accelerating the exciton separation and photogenerated electron transportation and improving the device stability. Abstract : Graphdiyne is introduced into perovskite film to construct a perovskite/graphdiyne bulk heterojunction for planar perovskite solar cells (PSCs). This bulk heterojunction could contribute an extra channel to accelerate the photogenerated carrier extraction and transportation, yielding a high power conversion efficiency (PCE) of 20.54% with excellent antimoisture stability. In addition, the PSCs can remain 95% of initial PCE under ambient condition after 140 d.